Identification and prevalence of gastrointestinal parasites among children aged 3-6 in Barangay Tunasan, Muntinlupa. - Rosales, Christian Lemuel D. 4 0 16; 5 (2007)
u
Thesis:(B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2007.
Keywords: 2 -- 0; 6; 20; 20; 2